IGNEOUS RIMS ON LOW-FEO AND HIGH-FEO CHONDRULES IN ORDINARY CHONDRITES - Krot A.N.; Wasson J.T. (My University, 1995)
Many ordinary chondrite (OC) chondrules are surrounded by rims that show evidence of appreciable melting and can be called igneous; these rims formed after the melting and solidification of the host chondrule. We studied thirteen igneous rims on low-FeO chondrules (Fa or Fs < 10 mol%) and nine rims on high-FeO chondrules (Fa or Fs > 10 mol%) in ordinary chondrites of petrographic type =< 3.5 by electron-microprobe analysis and scanning-electron microscopy. In both sets, olivine and pyroxene compositions of the rims are similar to or moderately higher in FeO than those in the host. Igneous rims around low-FeO chondrules show evidence of large degree (> 80%) melting including: (1) resorbed chondrule surfaces, (2) rounded metal/troilite nodules and feldspathic mesostasis, (3) euhedral and subhedral morphology of olivine and pyroxene and limited ranges in grain sizes, and (4) a rarity of relict grains. Most low-FeO chondrules have olivine as their major phase, but pyroxene is commonly the predominant phase in their rims. Rims on high-FeO chondrules generally have smaller grain sizes and exhibit lower degrees of melting than rims around low-FeO chondrules; Mg-rich relict grains are observed in high-FeO rims. Most low-FeO chondrules have matrix-like rims around the igneous rims, but matrix-like rims are rare around rims on high-FeO chondrules.There is a continuum between igneous rims and enveloping secondaries of compound chondrules; the existence of both sets of objects supports the view that, in the OC region, most mm-size grain assemblages experienced more than one melting event. The precursors melted to produce the igneous rims on low-FeO chondrules differ from those that comprise the rims on high-FeO chondrules. A sizeable fraction of the precursors of low-FeO rims are from the host chondrule. Most high-FeO rims appear to consist largely of melted matrix-like materials. If the rim precursors are mainly independent, the similar Fa and Fs contents in mafic minerals of rims and host chondrules indicate that (1) OC nebular subregions (bounded in space and/or in time) were dominated by well-mixed solids, (2) many chondrules experienced multiple heating events during a short period, and were then withdrawn from the chondrule-forming region, and (3) chondrules formed at different times were mixed before agglomeration to form chondrites. If the host chondrules were the main source of the low-FeO rim materials, the fact that pyroxene is generally more abundant than in the host suggests that SiO2-normative matrix was also an important ingredient and/or that kinetics favored pyroxene crystallization in the rim. Rims around high-FeO chondrules were heated to lower temperatures than rims around low-FeO chondrules. The rarity of matrix-like rims around high-FeO igneous rims may indicate that the dust-chondrule ratio was lower where they formed.